Morphology and Compatibility in Blends of Poly(vinyl methyl ether) and Poly(ε-caprolactoneblock- butadiene) Copolymer - YIPING, HUANG; XIAORONG, LIU; YANG, CAO; YUAN, HU; GUANGMEI, CHEN (Asian Journal of Chemistry, 2010)
The morphology and compatibility of the poly(vinyl methyl ether) (PVME) with poly(ε-carpolactone-block-butadiene) copolymer (PCL-b-PB) have been studied by polarized light microscope (PLM), differential scanning calorimetry (DSC) and Fourier transform infrared (FTIR). In the PVME/PCL-b-PB blends, ring-banded spherulites have been observed at various compositions and crystallization temperatures from 33 to 42ºC. The FTIR studies revealed that some weak interaction existed between PVME and the PCL-b-PB. The thermal analysis displayed the blends presented a single glass transition temperature (Tg) at each composition. The fraction of PCL that crystallized in the blends increased with increasing the PVME content up to about 40 wt% of PVME. The crystallization ability of PCL block in the blends was affected by PVME content. The dSC results indicated that PVME was partially compatible with the PCL-b-PB. The existence of some weak interaction and partial compatibility in the PVME/PCL-b-PB blends had influence on the formation of PCL ring-banded spherulites. Moreover, the existence of PB block affected the crystallization behaviour of PCL.